1970
DOI: 10.1620/tjem.101.141
|View full text |Cite
|
Sign up to set email alerts
|

Protein Metabolism in Cornea from Hypophysectomized Rats

Abstract: Hypophysectornized Rats. Tohoku J. exp. Med., 1970, 101 (2), 141-145-The effects of hypophysectomy and of growth hormone administration on in vitro incorporation of 14C-labeled leucine into protein of isolated rat cornea were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the current study, as the CCT values were similar in acromegaly and control groups, higher CH and CRF values in the acromegaly group were possibly related to structural changes in the cornea due to hormonal factors. Growth hormone deprivation by hypophysectomy in rats reported to be diminishing the amino acid pool of the cornea, and the diminution could be counteracted by the administration of growth hormone 5. Hypersecretion of growth hormone and IGF-1 are hallmarks of acromegaly 22.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, as the CCT values were similar in acromegaly and control groups, higher CH and CRF values in the acromegaly group were possibly related to structural changes in the cornea due to hormonal factors. Growth hormone deprivation by hypophysectomy in rats reported to be diminishing the amino acid pool of the cornea, and the diminution could be counteracted by the administration of growth hormone 5. Hypersecretion of growth hormone and IGF-1 are hallmarks of acromegaly 22.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of riboflavin, folic acid and vitamin E sometimes cause opacity in the lens of experimental animals (14-16). We have demonstrated that feeding on an excess glucose diet for a long period of time depresses the incorporation of 14C-leucine into the protein-fraction of rat lens (17).…”
Section: Discussionmentioning
confidence: 91%